Receipt for donation from Kleiderkammer der Judischen Gemeinde - Kleiderkammer der Judischen Gemeinde (1934)
Receipt of donation from Kleiderkammer der Judischen Gemeinde to Max Albert Bredig (1902-1977). Kleiderkammer der Judischen Gemeinde, was a organization that provided clothing for Jewish people in need.
Keywords: Bredig, Max Albert, 1902-1977; Gifts; Jews